Molecular evidence for the export of terrigenous organic matter to the north Gulf of Mexico by solid-state 13C NMR and Fourier transform ion cyclotron resonance mass spectrometry of humic acids. (15th January 2022) - Ware, Sarah A.; Hartman, Blaine E.; Waggoner, Derek C.; Vaughn, Derrick R.; Bianchi, Thomas S.; Hatcher, Patrick G.
Abstract: Sediment samples along a transect extending from the Mississippi River Birdsfoot Delta to the Mississippi Canyon on the Louisiana continental shelf were examined, by advanced analytical techniques, electrospray ionization coupled to a 12T Fourier transform ion cyclotron resonance mass spectrometer (ESI-FTICR-MS) and quantitative solid-state multiple cross polarization magic angle spinning (multi-CPMAS) 13 C NMR, in an effort to understand the source and export of terrigenous organic matter to the Gulf of Mexico. Both NMR and mass spectral data indicate that condensed aromatics (CA) and carboxyl-containing aliphatic molecules (CCAM) are present at the mouth of the river, reflective of high contributions from terrigenous soil-like organic matter. Mass spectral peak magnitudes of CA diminish by 15%, with increasing distance offshore, and represent 30% of integrated NMR peak areas. In contrast, mass spectral and NMR CCAM peaks increase by 7 and 13%, respectively. These trends in humic acid extracts, provide novel molecular evidence of terrigenous organic matter deposition in offshore sediments.